2007
DOI: 10.1111/j.1365-2222.2007.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of immunoglobulin E‐binding epitopes of β‐casein and β‐lactoglobulin showed a heterogeneous pattern of critical amino acids between individual patients and pooled sera

Abstract: These results indicate that AAs critical for IgE binding are more heterogeneous than initially defined by pooled milk-allergic patient sera. For future immunotherapeutic interventions with mutated peptides, critical AAs should also be identified with individual patient sera to account for heterogeneity of IgE binding between patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 20 publications
5
32
1
1
Order By: Relevance
“…Aggregation has earlier been suggested to be the reason for the sustained allergenic capacity of digestion products of allergens, which in theory were too small to contain two epitopes and thereby not big enough to cross-link two IgE molecules bound to the surface of mast cells or basophils [11,16,26]. The finding that IgE epitopes on BLG survive digestion is in accordance with previous studies stating that the major IgE epitopes reported in the literature by Järvinen et al [6] and Cocco et al [5] corresponded to areas of BLG where peptides did resist simulated gastro-duodenal digestion [22]. This is in agreement with the current study and could support the presence of major linear B cell epitopes on BLG.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Aggregation has earlier been suggested to be the reason for the sustained allergenic capacity of digestion products of allergens, which in theory were too small to contain two epitopes and thereby not big enough to cross-link two IgE molecules bound to the surface of mast cells or basophils [11,16,26]. The finding that IgE epitopes on BLG survive digestion is in accordance with previous studies stating that the major IgE epitopes reported in the literature by Järvinen et al [6] and Cocco et al [5] corresponded to areas of BLG where peptides did resist simulated gastro-duodenal digestion [22]. This is in agreement with the current study and could support the presence of major linear B cell epitopes on BLG.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have been performed with the aim of identifying BLG-specific epitopes. They indicate that many conformational as well as many linear epitopes exist, covering most of the molecule [5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…3B). Although alanine scanning is usually performed to determine the binding epitope, conversion to other amino acids has been utilized in some reports (33)(34)(35) when alanine might be included in the epitope. Therefore, we further changed Ala42 and Ala46 to other amino acids such as Ser and Val (Fig.…”
Section: Immunohistochemical Analysis Using Lpmab-13mentioning
confidence: 99%
“…Terms & Introduction b-Lactoglobulin (BLG) is a major food allergen, contributing significantly to the overall allergenicity of bovine milk (Besler, Eigenmann, & Schwartz, 2002). Sequential and conformational epitopes may play an important role in the allergenicity of this protein (Cocco, Jarvinen, Han, Beyer, & Sampson, 2007). Immunological investigations of BLG have reported six different IgE-binding regions (epitopes) of the protein that were linked with allergic reaction (Niemi et al, 2007).…”
Section: Allergenic Changes In β-Lactoglobulin Induced By Microwave Imentioning
confidence: 99%